Effect of wildfires on soil respiration in three typical Mediterranean forest ecosystems in Madrid, Spain (PLANT AND SOIL, 2013)
Mediterranean forests are vulnerable to numerous threats including wildfires due to a combination of climatic factors and increased urbanization. In addition, increased temperatures and summer drought lead to increased risk of forest fires as a result of climate change. This may have important consequences for C dynamics and balance in these ecosystems. Soil respiration was measured over 2 successive years in Holm oak (Quercus ilex subsp. ballota; Qi); Pyrenean Oak (Quercus pyrenaica Willd; Qp); and Scots pine (Pinus sylvestris L.; Ps) forest stands located in the area surrounding Madrid (Spain), to assess the long term effects of wildfires on C efflux from the soil, soil properties, and the role of soil temperature and soil moisture in the variation of soil respiration. Soil respiration, soil temperature, soil moisture, fine root mass, microbial biomass, biological and chemical soil parameters were compared between non burned (NB) and burned sites (B). The annual C losses through soil respiration from NB sites in Qi, Qp and Ps were 790, 1010, 1380 gCm(-2) yr(-1), respectively, with the B sites emitting 43 %, 22 % and 11 % less in Qi, Qp and Ps respectively. Soil microclimate changed with higher soil temperature and lower soil moisture in B sites after fire. Exchangeable cations and the pH also decreased. The total SOC stocks were not significantly altered, but 6-8 years after wildfires, there was still measurably lower fine root and microbial biomass, while SOC quality changed, indicated by lower the C/N ratio and the labile carbon and a relative increase in refractory SOC forms, which resulted in lower Q(10) values. We found long term effects of wildfires on the physical, chemical and biological soil characteristics, which in turn affected soil respiration. The response of soil respiration to temperature was controlled by moisture and changed with ecosystem type, season, and between B and NB sites. Lower post-burn Q(10) integrated the loss of roots and microbial biomass, change in SOC quality and a decrease in soil moisture.